Identification of neuronal enhancers of the proopiomelanocortin gene by transgenic mouse analysis and phylogenetic footprinting - Silva Junqueira de Souza, Flavio (2005)
The proopiomelanocortin (POMC) gene is expressed in the pituitary and arcuate neurons of the hypothalamus. POMC arcuate neurons play a central role in the control of energy homeostasis, and rare loss-of-function mutations in POMC cause obesity. Moreover, POMC is the prime candidate gene within a highly significant quantitative trait locus on chromosome 2 associated with obesity traits in several human populations. Here, we identify two phylogenetically conserved neuronal POMC enhancers designated nPE1 (600 bp) and nPE2 (150 bp) located approximately 10 to 12 kb upstream of mammalian POMC transcriptional units. We show that mouse or human genomic regions containing these enhancers are able to direct reporter gene expression to POMC hypothalamic neurons, but not the pituitary of transgenic mice. Conversely, deletion of nPE1 and nPE2 in the context of the entire transcriptional unit of POMC abolishes transgene expression in the hypothalamus without affecting pituitary expression. Our results indicate that the nPEs are necessary and sufficient for hypothalamic POMC expression and that POMC expression in the brain and pituitary is controlled by independent sets of enhancers. Our study advances the understanding of the molecular nature of hypothalamic POMC neurons and will be useful to determine whether polymorphisms in POMC regulatory regions play a role in the predisposition to obesity.